A review focus on the latest research progress of vitamin D in brain science - Liu, Ziming (Transactions on Materials, Biotechnology and Life Sciences, 2023)
Vitamin D is a hormone precursor that is increasingly recognized for its broad impact, including on brain health. Vitamin D regulates neurotrophic growth factors and influences inflammation and thrombosis; all of which affect neurocognition. Lack of vitamin D can cause osteoporosis, decreased bone density, and fractures. The flesh of fatty fish and fish liver oils are the finest sources of vitamin D. Any mixture of calcifediol, obtained from vitamin D3, and ercalcidiol, derived from vitamin D2, is known as 25-hydroxyvitamin D, also known as 25(OH)D. Loss of cognitive abilities including thinking, remembering, and reasoning is referred to as dementia. Some dementia patients have emotional instability and personality changes. The most common type of dementia is Alzheimer's disease. The condition is gradual, starting with minor memory loss and potentially progressing to the loss of communication and environmental awareness. One of the characteristics of Alzheimer's disease, amyloid beta (Aβ) aggregates, are known to be cleared by vitamin D. Additionally, vitamin D may offer neuroprotection against tau hyperphosphorylation brought on by A. As a result, dementia and Alzheimer's disease are more likely to develop in those with low vitamin D levels. A stroke, also known as a brain attack, happens when a blood artery in the brain breaks or when something stops the flow of blood to a specific area of the brain. Parts of the brain suffer harm or degeneration in either scenario. In addition, the risk of stroke may be raised by vitamin D deficiency.